Answer:
The answer is;
4^3/10 • x^9/10 •y^3/5
Step-by-step explanation:
We want to express the expression in the bracket in radical form;
(4x^3y^2)^3/10
What we shall do here is to multiply all the powers of the terms in the bracket by 3/10
So we shall have;
4^3/10 • x^(3*3/10) * y^(2*3/10)
= 4^3/10 • x^9/10 • y^3/5
x² - 14x + 46 = 0
subtract 46 from both-side
x² - 14x = -46
Add the square of the half of the co-efficient of x
x² - 14x + (-7)² = -46 + 7²
(x-7)² = -46 + 49
(x-7)² =3
Take the square root of both-side
x-7 = ±√3
x-7= ±1.732
Add 7 to both-side of the equation.
x= 7 ± 1.732
Eithe x= 7 + 1.732 or x= 7 - 1.732
x=8.732 or x=5.268
Therefore x = 8.732 , 5.268
The lower number of the fraction is the X value and since it's negative u go 3 to the right(if u loon at point T)and since it's a negative 4 on the top you go 4 down and if you would reverse it you would notice that 0|4 is 1 y value below the straight line so the coordinates are (3|5)
Answer:
t = 51 - 25p
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality<u>
</u>
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
25p + 1t = 51
<u>Step 2: Solve for </u><em><u>t</u></em>
- [Subtraction Property of Equality] Subtract 25p on both sides: 1t = 51 - 25p
- Simplify: t = 51 - 25p
Answer:
C. 48 Feet
Step-by-step explanation:
9 X 4 = 36
Triangle 1 : 4 X 3 = 12/2 = 6
Triangle 2 : 4 X 3 = 12/2 = 6
36 + 6 + 6 = 48